Character Education in the Perspective of the Qur'an - Haidar Rifqi Ghassany; Hendri Happy Firdaus (Penerbit Hellow Pustaka, 2024)
. Character education based on religious ethical values, these teachings are considered urgent to be developed as basic capital to form superior character humans, actively playing a role in realizing a peaceful society and a dignified nation. Education in the Qur'an emphasizes the aspect of morality. Verses that contain emphasis on cognition are determined by morality, as well as those things are ritualistic, such as prayer which is one aspect of the ritual that is directly related to God. The concept of education in the Qur'an is implied by the use of the terms tarbiyah, ta'lim, tadris, ta'dib and tazkiyah. In terms, it can be understood that the Prophet Muhammad SAW as a source of role models always tried to educate his people to be able to read and express themselves regarding the meaning contained in the Qur'an and to be able to practice it. Five important terms in providing a clear concept of character education from the perspective of the Qur'an which aims to form pious humans, people who have divine values ​​in themselves. To achieve this goal, the Qur'an provides an overview of the use of various approaches, methods and steps in character education. Implementation and results can be seen in the stories of the prophets in inviting and educating their people.